Pemanfaatan Media Internet dalam Pembelajaran Pai Selama Covid-19 Di MTsN 1 Aceh Besar - Ramadon Ramadon; Ainul Mardhiah (2021)
This study aims to determine the use of internet media in PAI learning during Covid-19 at MTsN 1 Aceh Besar. By using descriptive qualitative research methods. The use of internet media is very helpful in the learning process during the Covid-19 pandemic at MTsN 1 Aceh Besar. Advances in information technology that are very advanced at this time, internet media can connect students with teachers through whatsapp pages, whatsapp groups, youtube. Supporting factors for the use of internet media in PAI learning during Covid-19 at MTsN 1 Aceh Besar are the school principal's policy that strongly supports the online learning process, support from parents and the Tri internet card given from the school as a result of a proposal from the government that has been recorded. number in the Ministry of Education and Culture for teachers and students. While the obstacle factor is that not all students have cellphones and networks that are difficult to reach.